Evaluation of congruence among dietary supplement use and motivation for supplementation in young, Canadian athletes - Parnell, J.; Wiens, K.; Erdman, K. (Journal of the International Society of Sports Nutrition, 2015)
Background: Dietary supplement use is endemic in young athletes; however, it is unclear if their choices are congruent with their motivation for supplementation and the established benefits of the dietary supplements. The aim of this study was to evaluate the relationships between dietary supplement use and self-reported rationale in young athletes. Methods: Canadian athletes (n = 567; 11-25 years; 76 % club or provincial level, 24 % national or higher) completed a questionnaire designed to assess supplementation patterns and motivation for supplementation. Chi square tests examined associations between dietary supplements and self-reported rationale for use. Results: Vitamin and mineral supplements, including vitamin-enriched water, were associated with several health- and performance- related reasons (p < 0.001). Branched chain amino acids (BCAA) and glutamine were linked to improving diet and immune function (p < 0.01), but were more strongly associated with performance reasons, as were performance foods (protein powder, sport bars, sport gels, etc.). Plant extracts and fatty acids were primarily associated with health reasons, particularly immune support (p < 0.001). Conclusions: Congruencies exist between performance rationales and supplementation for common ergogenic aids, however, less so for vitamin and mineral supplements, vitamin-enriched water, and plant extracts. Incongruences were found between fatty acids, protein supplements, vitamin and mineral supplements, vitamin-enriched water, and plant extracts and health motivators for supplementation. Educational interventions are essential to ensure young athletes are using dietary supplements safely and effectively.